Faculty development needs assessment for online teaching - Elsamanoudy, Ayman Z.; Abou-Kamer, Rasha; Ghoneim, Fatma M.; El-Saadany, Sherif; Soliman, Mona A.; Hassanien, Mohammed A. (International Journal Of Community Medicine And Public Health, 2018)
Background: Academic staff members, who are responsible for teaching and training, should be aware of the principle of online course design, development, and implementation. The aim of this study is to evaluate instructors’ skills and needs for conducting distance learning healthcare courses, including the level of assistance they need to implement and use online and software tools in online courses. Methods: The current study applied online faculty survey used by the Center for Teaching Excellence, University of South Carolina to assess the faculty’s instructional technology needs for training and support. The survey asked faculty staff about a broad number of classroom and online technologies, with a helpful response scale that reveals not only what the faculty is already using, but also what the instructors want to use and what they need help with. Results: The results of this study revealed a significant need of faculty staff members for the training and development of their skills in almost all tools used for conducting online courses. The female responder was higher than males. Regarding the use of software, although the majority of participating staff members in this study use almost all software tools required for conducting online healthcare courses, they expressed a need for help in developing new ideas to use the software effectively. Conclusions: From this study, it could be concluded that it is essential to organize comprehensive faculty development training courses for staff members to help them in conducting their online courses or converting their face-to-face courses to blended courses effectively.